Knapsack problems in products of groups. (May 2016) - Frenkel, Elizaveta; Nikolaev, Andrey; Ushakov, Alexander
Abstract: The classic knapsack and related problems have natural generalizations to arbitrary (non-commutative) groups, collectively called knapsack-type problems in groups. We study the effect of free and direct products on their time complexity. We show that free products in certain sense preserve time complexity of knapsack-type problems, while direct products may amplify it. Our methods allow to obtain complexity results for rational subset membership problem in amalgamated free products over finite subgroups.